Analysis of the Application of Game-Based Learning Methods on Students' Mathematics Learning Outcomes in Grade V of SDN 2 Bentek in the 2024/2025 Academic Year - Tiratul Aini; Nunung Mardianti; Tuti Alawiyah (Jurnal Ilmiah Mandala Education (JIME), 2025)
This study focuses on analysing the application of game-based learning methods in mathematics learning in fifth grade elementary school. In addition, this study also aims to identify factors that influence the effectiveness of applying game-based learning methods in mathematics learning and to describe the impact of applying game-based learning methods in improving mathematics learning outcomes. The research method used is qualitative research with a descriptive type and employs the Miles and Huberman design model.The research results indicate that the implementation of Game-Based Learning (GBL) in mathematics education has proven effective in enhancing student engagement and learning outcomes. This approach aligns with Csikszentmihalyi's Flow Theory and Piaget-Vygotsky's Constructivism Theory, where learning through games fosters full engagement and deeper conceptual understanding. The implementation of Game-Based Learning through systematic stages—from planning, preparing materials, conducting interactive activities, to reflection—successfully creates a enjoyable and meaningful learning environment. Indicators of success include students' ability to connect abstract concepts with games, increased group participation, and positive student responses. However, its effectiveness heavily depends on time management, availability of teaching materials, student enthusiasm, and adequate facilities and resources. The positive impact of the game-based learning method is evident in increased motivation, activity, and understanding of mathematics among students, while also developing logical and collaborative thinking skills. Although it requires extra preparation regarding media and time, its benefits in creating interactive and contextual learning make the game-based learning method an innovative alternative. For optimization, teachers need to adapt this method to classroom conditions and address its weaknesses through careful planning. Thus, the game-based learning method can be applied as a dynamic mathematics learning strategy, especially at the elementary school level, to achieve effective and memorable learning outcomes.